Scenario Simulation of Ecosystem Services Based on Land Use/Land Cover Change in the Bailong River Basin, in China - Shuangying Li; Yanyan Zhou; Dongxia Yue; Zhongling Guo; Zhi Li (Land)
Land use/land cover changes (LUCCs) significantly reshape ecosystem services (ESs) within the framework of climate change. Studying LUCC and its impact on ESs is crucial for a comprehensive understanding of the impact of human activities on ecosystems. The InVEST model coupled with the predicted land use data were used to analyze the spatiotemporal characteristics of four ESs (soil conservation (SC), water yield (WY), carbon storage (CS), and habitat quality (HQ)) under three scenarios from 2040 to 2100 and quantified trade-offs/synergies and bundles of these ESs within the Bailong River Basin (BRB). The results indicated that (1) under the SSP1-2.6 scenario, there is an anticipated increase in forestland, a concurrent decrease in grassland, farmland, and built-up land, and an enhancement in four ESs from 2040 to 2100. The forestland and farmland in the SSP2-4.5 scenario showed a gradual decrease, with an expansion of grassland and built-up land. Except for HQ, the other three ESs were reduced. Both forestland and grassland decreased. Built-up land and farmland increased, and ESs decreased significantly under the SSP5-8.5 scenario. (2) Synergistic effects were identified among the ESs, with the most pronounced synergy observed between CS and HQ. Spatially, six pairs of ESs under the SSP1-2.6 scenario showed synergistic effects. Under the SSP2-4.5 and SSP5-8.5 scenarios, most of the ESs present trade-off effects. (3) The characterization of ES bundles revealed that the balanced enhancement of the four ESs predominantly occurred in the southern region of the basin. Among the scenarios, SSP1-2.6 had the highest representation, followed by the SSP2-4.5, while the SSP5-8.5 had the lowest proportion. The findings facilitate the sustainable and balanced development of diverse ESs and offer theoretical and technical insights for devising spatial regulation policies and ecosystem-based management strategies.